2017
DOI: 10.15446/ing.investig.v37n1.57983
|View full text |Cite
|
Sign up to set email alerts
|

Innovative approach for achieving of sustainable urban water supply system by using of solar photovoltaic energy

Abstract: This paper describes and analyses new and innovative concepts for possible integration of solar photovoltaic (PV) energy in urban water supply system (UWSS). The proposed system consists of PV generator and invertor, pump station and water reservoir. The system is sized in such a manner that every part of it is sized separately and then, integrated into a whole. This integration is desirable for several reasons; the most important is the success of the objectives of sustainable living in urban areas i.e., achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…growth rates, rapid urbanization, and an inefficient sewerage system are also imparting immense pressure on the quality and quantity of existing water sources. Consequently, the need for water to increase food production has rapidly increased [5][6][7]. Therefore, the effluents generated from different sources are being used without treatment for agriculture purposes in order to cope with increasing water scarcity in many parts of the country, including in Multan District [8], which is considered to be an influential, political, and agricultural centre of Pakistan covering an area of 304 km 2 with a population of 1.9 million.…”
mentioning
confidence: 99%
“…growth rates, rapid urbanization, and an inefficient sewerage system are also imparting immense pressure on the quality and quantity of existing water sources. Consequently, the need for water to increase food production has rapidly increased [5][6][7]. Therefore, the effluents generated from different sources are being used without treatment for agriculture purposes in order to cope with increasing water scarcity in many parts of the country, including in Multan District [8], which is considered to be an influential, political, and agricultural centre of Pakistan covering an area of 304 km 2 with a population of 1.9 million.…”
mentioning
confidence: 99%
“…They found that SPVWP systems are more economically viable than diesel and conventional electricity grid-based pumping systems for irrigation and water supply in rural, urban and remote areas. Margeta & Ðurin (2017) proposed a system consisting of a PV module, an invertor, a pump station, and a reservoir to describe and analyse new and innovative concepts for possible integration of solar energy in urban water supply systems. It was shown that the proposed concepts for local energy production and use are applicable and sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Not only will this give better optimization of such a system, but it would lead to energy conservation. One characteristic of UWSS is that water consumption goes hand in hand with energy consumption, since energy is required for water production, treatment and distribution, and wastewater collection and treatment [1]. It means that utilities buy most energy at the highest price during the day.…”
Section: Introductionmentioning
confidence: 99%